Bioutilização de resíduo agroindustrial (crueira) para produção de etanol de segunda geração - Costa, Sharlene Silva (2016)
The use of agro-industrial waste in biotechnological processes is gaining prominence for production of renewable biofuels through of modern, economic and sustainable technologies. The agro-industrial residues rich in starch have been studied for presenting a great potential for the production of bioethanol. Among the main starchy residue is the crueira, which is a solid produced in abundance after the grinding and flaking of the cassava processed to obtain flour. For the bioconversion of starch contained in the crueira is needed a saccharification process, which was conducted in this study using an enzyme extract produced by Bacillus sp. The fermentable sugars produced in the hydrolysis, were later converted by the yeast Saccharomyces cerevisiae, producing ethanol as the final product. Therefore, the objective of this research was to study re-use of agro-industrial waste (crueira) for second-generation ethanol. The residue was characterized through physical-chemical analysis and the study of enzymatic hydrolysis process was made by Experimental Full Factorial Planning 22 . Then, the hydrolyzate was used to the fermentation process. The results of the physico-chemical analysis showed that crueira has a high starch content (82.00 ± 0.58%). Through the Experimental Planning, it was evident that the variable concentration of crueira was statistically significant, with the best saccharification range obtained at 100 to 108 g / L crueira and 70 mL of enzymatic extract reaching 10 ° Brix. Kinetic studies demonstrated that 20 hours is the time required to complete the hydrolysis process. The alcoholic fermentation studies showed 0.291% ethanol content, having different physical and chemical characteristics of the produced ethanol from sugarcane.